Consultation workshop on NAFRI’s five-year research strategy for agriculture, forestry, and rural development (2026-2030) in Lao PDR - International Water Management Institute (CGIAR, 2024)
IWMI, under CGIAR Initiatives on Agroecology and National Policies and Strategies (NPS), supported the National Agriculture and Forestry Research Institute (NAFRI) in organizing a consultation workshop to shape NAFRI’s five-year research strategy for 2026-2030, focusing on agriculture, forestry, and rural development.